PEMBELAJARAN MENGEKSPRESIKAN PUISI DALAM BENTUK TEATER MENGGUNAKAN METODE DIRECT INSTRUCTIONS PADA KEGIATAN EKSTRAKURIKULER TEATER DI SMP NEGERI 1 BOTUMOITO - Tou, Mikshera; Pulukadang, Mimy Astuty; Semiaji, Trubus; Djafar, Nurlia; Ohi, Rahmawati (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research is motivated by the unsatisfactory learning outcomes of arts and culture subject at SMP Negeri 1 Botumoito. This issue is due to the lack of students' understanding and skills in learning theater arts. Based on interviews conducted with the arts and culture subject's teacher (Mirnawati Bolio, S.Pd, September 2023), students' lack of interest in theater art is caused by limited knowledge and low confidence in performing it publicly. Therefore, the researcher is motivated to conduct research at the school. This research uses the Direct Instructions method, where the researcher teaches directly or demonstrates theater performances in front of the class, focusing on the theme of